Valves with flow control by synthetic jets - Tesař, Václav; Broučková, Zuzana; Kordík, Jozef; Trávníček, Zdeněk; Peszynski, Kazimierz (EPJ Web of conferences, 2012)
Synthetic jets are currently in the focus of attention as means for flow control in external aerodynamics. Less known and studied is their use in internal aerodynamics, where several existing papers discussed separation control in diffusers. The subject of this paper, however, is a completely new idea — using the synthetic jet in flow control valves having no moving components. The valve considered would operate as a bistable diverter: by the action of the synthetic jet, the controlled fluid is deflected into one of available two flowpaths. A preliminary experiment performed with an axisymmetric valve version demonstrated viability of the idea.